Identification of in vitro metabolites of a new anticoccidial drug nitromezuril using HepG2 cells, rat S9 and primary hepatocytes by liquid chromatography/tandem mass spectrometry. (20th June 2014) - Zhang, Keyu; Li, Sumei; Zheng, Wenli; Zhang, Lifang; Wang, Chunmei; Wang, Xiaoyang; Fei, Chenzhong; Xue, Feiqun; Wang, Mi
<x xml:space="preserve">Abstract</x> RATIONALE Nitromezuril is a novel triazine compound possessing remarkable anticoccidial activity that could have possible future use in the prevention of coccidiosis; however, its metabolic characteristics have still not been revealed. METHODS In the present study, the in vitro metabolism of nitromezuril in HepG2 cells, rat S9 and primary hepatocytes was investigated using high‐performance liquid chromatography with electrospray ionization tandem mass spectrometry. The structures of metabolites and their product ions were easily and reliably characterized based on the accurate MS2 spectra and known structure of nitromezuril. RESULTS As expected, three metabolites (M1–M3) were detected in a HepG2 cells system, one metabolite was respectively detected and identified as M1 in rat S9 and M2 in rat primary hepatocytes. M1 and M2 were confirmed respectively based on comparing their retention times, full scan, product ion scan with available authentic standards and M3 was tentatively identified as hydroxyl compound of M2. CONCLUSIONS Pathways of nitromezuril were reported for the first time and no obvious species difference was shown. The proposed metabolic pathways of nitromezuril can be expected to play a key role in pharmacodynamics and food safety evaluations. Copyright © 2014 John Wiley & Sons, Ltd.